Impact of Acetic Acid on HPV Testing Using Hybrid Capture 2. Issue 4 (October 2018) - Pina, Annick; Sauthier, Philippe; Coutlée, François; Trottier, Helen; Mayrand, Marie-Hélène
Objectives: As per the American Society for Colposcopy and Cervical Pathology guidelines, human papillomavirus (HPV) testing is currently used as part of cervical cancer screening and during colposcopy follow-up. The present project evaluated if the application of acetic acid (AA) impacts HPV test results. Methods: We conducted a prospective nonrandomized interventional study. Participants referred for colposcopy were eligible if immunocompetent, older than 18 years, and not pregnant. Women in group A (controls) received 2 consecutive HPV tests without application of AA. Women in group B had a first HPV sample collected before the application of AA and a second sample collected 3 minutes after application of AA. Samples were tested for HPV DNA with Hybrid Capture 2 (HC2) according to the manufacturer's instructions. Results: From October 17, 2012, to January 10, 2013, approximately 101 women were recruited in 2 colposcopy clinics. In each group, concordance was 98%, with only 1 participant having discordant results (testing negative on the first sample and positive on the second sample). We found no statistically significant difference in relative light units(RLUs) between groups (median of difference, − 0.02 vs −0.05 RLU; p = .93). Conclusions: The results of this study suggest that acetic acid at concentrations of 3% to 5% and sequential cervical sampling do not modify the result of HPV testing by Hybrid Capture 2. Abstract : Acetic acid at concentrations of 3% to 5% and sequential cervical sampling do not modify the results of HPV testing by Hybrid Capture 2.